2012
DOI: 10.1186/1477-7819-10-75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment clinical factors on overall survival in glioblastoma multiforme: a Surveillance Epidemiology and End Results (SEER) population analysis

Abstract: BackgroundGlioblastoma Multiforme (GBM) is one of the most aggressive primary brain tumors and is associated with a dismal prognosis. The median survival after the primary diagnosis remains poor, even after multimodal treatment approaches. However, a few patients have been reported to have long term survival greater than three years. A number of studies have attempted to define factors capable of predicting long term outcomes in specific patient groups. This article reports the outcomes of a very large group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 37 publications
4
49
1
2
Order By: Relevance
“…Nonetheless, such geoethnic variations are well described, such as in a number of population-based studies showing that the incidence of GBM is higher among Caucasians than other ethnic groups. (7,(10)(11)(12) However, there has been no conclusive evidence that the clinical outcomes of GBM differ among ethnic groups. (13) Population-based studies conducted in Korea and China showed that the survival of Asian patients was similar to that of Western populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, such geoethnic variations are well described, such as in a number of population-based studies showing that the incidence of GBM is higher among Caucasians than other ethnic groups. (7,(10)(11)(12) However, there has been no conclusive evidence that the clinical outcomes of GBM differ among ethnic groups. (13) Population-based studies conducted in Korea and China showed that the survival of Asian patients was similar to that of Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…(1,11,20) These factors include age, performance status, histology, extent of surgical resection, and the addition of radiotherapy and chemotherapy as adjuvants. Some authors have attempted to stratify patients into prognostic groups based on these factors in order to predict survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that patient age is a reliable predictor of overall survival following the initial diagnosis of GBM [10,11,19,30,39], but this study and others appear to suggest that it is not associated with survival differences following GKRS salvage (Tables 3 and 4) [15,18]. These data, along with the aforementioned RTOG-RPA comparison, suggest that older patients with favorable KPS scores are likely to appreciate similar post-salvage survival advantages as younger patients.…”
Section: Discussionmentioning
confidence: 48%
“…Factors which historically predict a more favorable prognosis for GBM patients are age less than 50, Karnofsky Performance Status (KPS) of 90 or better, and achieving gross total resection [10][11][12][13][14]. Additional studies have shown an improved prognosis for smaller volume tumors (<15cc), unifocal lesions, use of additional salvage therapies, and O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation, and Asian/Pacific Islander ethnicity [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%